Coming to terms with research practice: Riding the emotional rollercoaster of doctoral research studies - Morrison Saunders, A.; Moore, S.; Hughes, Michael; Newsome, D. (Routledge, 2010)
Emotions are an integral part of the doctoral process. A range of emotion are common and to be expected. How do emotions affect the doctoral process for both doctoral students and their supervisors? And how can they be made to work positively for all concerned? This chapter explores the role that emotions play in the doctoral process and how students can benefit from reflecting on this issue. The role of emotions at the beginning, middle and end of a doctoral programme is explored along with some of the emotions that arise from the supervisor/doctoral student relationship.